DNA-PKcs promotes fork reversal and chemoresistance - Dibitetto, Diego; Marshall, Shannon; Sanchi, Andrea; Liptay, Martin; Badar, Jumana; Lopes, Massimo; Rottenberg, Sven; Smolka, Marcus B (Molecular cell, 2022)
The DNA-PKcs kinase mediates the repair of DNA double-strand breaks via classical non-homologous end joining (NHEJ). DNA-PKcs is also recruited to active replication forks, although a role for DNA-PKcs in the control of fork dynamics is unclear. Here, we identify a crucial role for DNA-PKcs in promoting fork reversal, a process that stabilizes stressed replication forks and protects genome integrity. DNA-PKcs promotes fork reversal and slowing in response to several replication stress-inducing agents in a manner independent of its role in NHEJ. Cells lacking DNA-PKcs activity show increased DNA damage during S-phase and cellular sensitivity to replication stress. Notably, prevention of fork slowing and reversal via DNA-PKcs inhibition efficiently restores chemotherapy sensitivity in BRCA2-deficient mammary tumors with acquired PARPi resistance. Together, our data uncover a new key regulator of fork reversal and show how DNA-PKcs signaling can be manipulated to alter fork dynamics and drug resistance in cancer.